Behaviour of reinforced embankment on soft ground and reliablity analysis - Xu, Bo (2008)
Stability analysis of slopes or embankments is greatly affected by uncertainty of soil properties. The current design practice is based on the factor of safety which cannot directly reflect the input uncertainty. Probabilistic stability analysis is a rational way to incorporate uncertainty in the design procedure. Unfortunately, most geotechnical engineers are reluctant to adopt probabilistic techniques. The objective of this study is to provide a practical approach to integrate probabilistic analysis in the stability evaluation of reinforced embankments on soft ground.